The Jewish Question: Part I - Gans, Eric Lawrence (2021)
For Srulik I have long been a fan of Caroline Glick, the Chicago-born Israeli author of The Israeli Solution, and the sharpest commentator I know on Israeli politics and international relations. Not surprisingly, CG has remained a strong supporter of Netanyahu and is highly critical of the current coalition regime. The other day on her...